Students e-learning readiness towards education 4.0: Instrument development and validation - Didik Hariyanto; Sigit Yatmono; Moh Khairudin; Thomas Kí¶hler (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
One of the characteristics of Education 4.0, which is a response to the demands of Industry 4.0, is the use of adaptive and artificial intelligence technologies in online education. In relation to e-learning preparedness, many researchers have conducted studies. But in Education 4.0, the teaching and learning processes' peculiarities were not considered. Therefore, this study aims to develop and validate an instrument for assessing the e-learning readiness of students toward Education 4.0. There were 126 undergraduate students participated in this study. The respondents were asked to fill out the online-based questionnaire voluntarily. The data obtained were then statistically analyzed using the Pearson product-moment correlation test to measure the instrument's validity. The validity test showed that all items on the questionnaire are considerably valid at a significance level of 0.01. Meanwhile, the instrument reliability was measured through Cronbach's alpha score. The reliability test confirmed that six aspects out of seven of the instrument are categorized as high reliability (flexibility, learning preferences, project-based learning, data interpretation, improving curriculum, and self-directedness). One aspect (field experience) showed a moderate level of reliability. The study's findings confirmed that the questionnaire developed is valid and reliable for collecting data concerning the students' e-learning readiness toward Education 4.0.